Analysis of Team Situation Awareness Using Serious Game and Constructive Model-Based Simulation. Issue 19 (2016) - Sawaragi, Tetsuo; Fujii, Kohei; Horiguchi, Yukio; Nakanishi, Hiroaki
Abstract: In this study, analysis of team situation awareness using a serious game of supply chain management for steel production is provided. By tracing the development of the performances of the game made by two different teams, a comparative analysis is done with respect to team situation awareness shared within the team. Especially, we focus into the individual players' mental models that may evolve and grow as they accumulate a number of game sessions. From the acquired protocols of players during the sessions, players' temporal mental models of situation awareness are traced, then the progress of team situation awareness among the players are derived. Through a comparative analysis of the two different teams with respect to their shared team situation awareness, we discuss about the relationships between the maturity of the teams and performance scores attained by the teams. Finally, a simulation model for generating such multiple players' behaviors within a variety of teams is proposed. This is based upon a descriptive decision model of Garbage Can Model, and findings discovered during the gaming sessions are verified and generalized through a model-based constructive approach.